2001
DOI: 10.3168/jds.s0022-0302(01)74599-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma bovis in Preservative-Treated Field Milk Samples

Abstract: Control of mycoplasmal mastitis requires individual cow milk sampling for culture and identification of Mycoplasma bovis. This sampling is time-consuming and expensive. Currently, some herds sample cows monthly with the dairy herd improvement (DHI) program, but a preservative is added to this milk that kills M. bovis. In this paper, a nested polymerase chain reaction (PCR) procedure that allows for rapid testing of preservative-treated milk is validated. The specificity of the nested PCR assay was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 21 publications
2
31
0
2
Order By: Relevance
“…Although PCR-based platforms for the detection of mastitis pathogens directly in milk have been evaluated, 17,21 an extensive study of the ability of PCR assays to distinguish between Acholeplasma and Mycoplasma species using fieldbased milk samples has not been made. The results reported herein are consistent with previous findings that identified 2 PCR products for Acholeplasma species and 1 PCR product for all Mycoplasma species as described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PCR-based platforms for the detection of mastitis pathogens directly in milk have been evaluated, 17,21 an extensive study of the ability of PCR assays to distinguish between Acholeplasma and Mycoplasma species using fieldbased milk samples has not been made. The results reported herein are consistent with previous findings that identified 2 PCR products for Acholeplasma species and 1 PCR product for all Mycoplasma species as described.…”
Section: Discussionmentioning
confidence: 99%
“…25 Discrimination of Acholeplasma species from Mycoplasma species has been practiced using the digitonin and/or the nisin disc diffusion assay, and by PCR methods, for several years. 1,21,27 What is not known is how comparable are these tests of mollicute genera and how accurately these tests can discriminate between these genera. Several local and/or regional veterinary practices who manage their own diagnostic services have inquired on the utility of PCR or digitonin assays in Mycoplasma species identification.…”
Section: Introductionmentioning
confidence: 99%
“…21 DNA was extracted and identified by polymerase chain reaction (PCR) with the use of M. bovis-specific primers. 22 The PCR assay was performed by Prairie Diagnostic Services.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the sensitivity and specificity of PCR on bulk tank milk compared with cultures of the same samples are 100% and 99.8%, respectively (Baird et al, 1999). In the study by Pinnow and colleagues, the sensitivity of Nested-PCR for the detection of M. bovis in milk kept for 2 years, was 100%, while the sensitivity of culture was 27%; so this approach was introduced as an appropriate method to identify and isolate M. bovis in clinical samples (Pinnow et al, 2001). It was indicated that the identification of M. bovis strains in cattle herds and the evaluation of their pathogenicity and antigenic variation is important (Behrens et al, 1994).…”
Section: Mycoplasmamentioning
confidence: 99%